Association of plasminogen activator inhibitor-1 and angiotensin converting enzyme polymorphisms with recurrent pregnancy loss in Iranian women - Fatemeh Shakarami; Mohammad Taghi Akbari; Shohreh Zare Karizi (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: Recurrent pregnancy loss (RPL) defined by two or more failed pregnancies before 20 weeks of gestation. Several factors play a role in RPL including thrombophilic conditions which can be influenced by gene polymorphisms. Plasminogen activator inhibitor-1 (PAI-1) and angiotensin converting enzyme (ACE) genes are closely related to fibrinolytic process, embryonic development and pregnancy success. Objective: The aim of this study was to investigate the relationship between RPL and common polymorphisms in ACE and PAI-1 genes. Materials and Methods: In this case control study, 100 women with recurrent abortions (at least two) were selected as cases and 100 healthy women with two or more normal term deliveries without a history of abortion as controls. Total genomic DNA was isolated from blood leukocytes. The status of the PAI-1 4G/5G and ACE (D/I) polymorphism was determined by PCR-RFLP. Results: Homozygosity for PAI-1 4G polymorphism was seen in 17 cases (17%), and 5 controls (5%) (p=0.006) so patients with homozygote 4G mutation were significantly more prone to RPL in contrast to control group (OR: 4.63, % 95 CI: 1.55-13.84). In addition, 7 patients (7 %), and no one from the control group, were homozygote (I/I) for ACE polymorphism (p=0.034), suggesting no significant associations between ACE D allele or DD genotype and RPL. Conclusion: Considering these results, because 4G/4G polymorphism for PAI-1 gene could be a thrombophilic variant leading to abortion, analysis of this mutation and other susceptibility factors are recommended in patients with RPL.